Ethyl pyruvate inhibits LPS induced IPEC-J2 inflammation and apoptosis through p38 and ERK1/2 pathways. Issue 20 (18th October 2019) - Dong, Na; Xu, Xinyao; Xue, Chenyu; Wang, Chensi; Li, Xinran; Bi, Chongpeng; Shan, Anshan
ABSTRACT: The endotoxin of Gram-negative bacteria threatens the intestinal health of livestock. Ethyl pyruvate (EP) has been shown to regulate intestinal immunity and protect against cell and tissue damage. In this study, it was first verified that EP could reduce the secretion of IL-8, TNF-α, IL-6 and IL-1β in LPS-induced IPEC-J2 cells. Then, we used RNA sequencing (RNA-seq) to analyze the differentially expressed genes (DEGs) of inflammatory factors induced by LPS in IPEC-J2 cells. It was found that LPS induced the upregulation of 377 genes and the downregulation of 477 genes compared to Vehicle; LPS+EP induced the upregulation of 258 genes and the downregulation of 240 genes compared to Vehicle; and LPS+EP induced the upregulation of 373 genes and the downregulation of 188 genes compared to LPS (fold change > 1.5 and FDR < 0.01). Their enrichment pathways included the MAPK signaling pathway, PI3K-Akt signaling pathway, Toll-like receptor signaling pathway, and other pathways. Furthermore, the mRNA level of cytokines associated with inflammation and apoptosis enriched in the MAPK pathway was verified by qRT-PCR. Western blots and immunofluorescence revealed that EP significantly inhibited phosphorylated p38 and phosphorylated-ERK1/2 protein expression levels ( P < 0.05). The apoptosis due to LPS reduced by EP was significantly inhibited, as shown by Annexin V-FITC/PI staining. According to the results, EP inhibited the expression of IL-8, TNF-α, IL-6 and IL-1β as well as apoptosis by inhibiting the phosphorylation of p38 and ERK1/2 in LPS-induced IPEC-J2 cells.